The Earliest Horse Remains in Lithuanian Burial Sites - Merkevičius, Algimantas; Muradian, Lijana (Archaeologia Lituana, 2016)
The custom to bury horses in the East Baltic region spread after the birth of Christ. Horse graves found in the territory of Lithuania mostly date to the first millennium AD and the first half of the second millennium AD. However, origins of the custom to bury horses in the territory of Lithuania can be traced back to the Early Metal Period. In this article, the material of the earliest horse remains in burial sites found in the territory of Lithuania are analysed and interpreted. The earliest horse remains in funerary context were found in five mounds within three barrow cemeteries: Kurmaičiai, Kveciai and Ėgliškės, located in the western part of Lithuania – near Akmena, Tenžė, and Danė privers respectively. The barrow cemeteries were arranged within 3 to 7.5 kilometres of each other. Barrow mounds dating to the Early Metal Period usually contained only certain horse body parts rather than the whole skeleton. Four horse teeth were found in Kurmaičiai barrow mounds no. 8 and 11 – two on each mound. Kveciai barrow mound no. 1 contained a horse skull and a few unidentified horse bones. These bones were placed within a stone structure, which was probably disturbed at some point because the western part had only a few isolated stones left. The surviving stone structure on the eastern side was 2 metres long and 1 metre wide. Here it connected to the external stone circle of the barrow. Ėgliškiai barrow mound no. 1 contained unidentified disarticulated horse bones, scattered in a 1 square metre area between the central and middle stone circles. Barrow mound no. 2 contained several horse teeth, found near the external stone circle. Horse bones showed no signs of burning, even though cremation was the dominant burial custom during this period. Most of the barrow mounds contained cremated human remains, with the exception of mound no. 2 in Ėgliškiai, which contained two inhumations. Some cremated human remains were placed in urns with smooth or brushed surface; others were placed in small pits or surrounded by stone arrangements. Grave goods were scarce in cremation burials but they appear more frequently with inhumations. Horses were buried at a distance from human graves, so the remains of these animals were not associated with any specific human grave in the barrows. Furthermore, the horse grave in Kveciai was separated from human graves by a stone structure, which was very similar to the stone structures formed for human graves. It appears that in Kveciai barrow humans and horses were buried using the same symbols of material culture. The beginning of the custom to bury horses in Western Lithuania dates back to the end of the Late Bronze and Early Iron Ages. These changes in burial traditions are associated with the formation of special status of horses in the Baltic region during the second and first millennium BC.